PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MODEL SNOWBALL THROWING - Alia Z, Merry Zufdil; Alwi, Elma; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstrackThe purpose of this study is to describe theimprovemen of student learning outcomes on learning IPS by using model  Snowball Throwing student the classroom IV SDN 23 VII Koto Sungai Sarik Kab. Padang Pariaman on the student class IV who number 36 students. This research  uses qualitative and quantitative approach. The type of  research in classroom action research student learning outcomes cycle I  70,9 increase to 84,4 in cycle II. Therefore, the Snowball Throwing model can improve student learning outcomes in IPS learning in grade IV SDN 23 VII Koto Sungai Sarik Kab. Padang Pariaman.Keyword: Learning outcomes,IPS, and Snowball Throwing.